Pouch Function Over Time and With Advancing Age. Issue 2 (February 2022) - Lightner, Amy L.; Steele, Scott R.; McMichael, John P.; Jia, Xue; Qazi, Taha; Click, Benjamin H.; Church, James
Abstract : BACKGROUND: No long-term pouch studies have included follow-up >30 years or an analysis in patients >80 years old. OBJECTIVE: This study aimed to investigate pouch function and pouch failure in patients with a pouch in situ >30 years and in patients >80 years old. DESIGN: This is a retrospective review. SETTING: This study was conducted at an IBD referral center. PATIENTS: Adult patients with ulcerative colitis who underwent an IPAA between 1983 and 1990 were selected. MAIN OUTCOME MEASURES: The primary outcomes measured were pouch function and pouch failure rates. METHODS: Data collection included diagnosis, age at IPAA, indication for IPAA, medications at IPAA, pathology at the time of IPAA, postoperative morbidity, functional outcomes, quality of life, pouch excision or ileostomy and indication, and date of last follow-up. All living patients were contacted in April 2020 to retrieve functional data and pouch failure rates. RESULTS: A total of 566 patients had a pouch constructed between 1983 and 1990; of the 145 at most recent contact, 75 had their pouch in situ ≥30 years and 14 were ≥80 years old. Mean age at diagnosis was 25.8 years (10.6 SD), age at surgery was 34.7 years (11.3 SD), and age at last follow-up was 60.5 years (13.2 SD). At a median of 30 years (IQR, 21–32), 145 patients responded to the functional survey. Significantly increased rates of urgency (always, mostly, sometimes: 71.5% vs 23.5%) and seepage during the day (71.4% vs 22.4%) were observed in patients ≥80 years. In patients ≥80 years with a pouch in situ ≥30 years, urgency and incontinence were sometimes experienced by nearly 50% and pouch failure occurred in one third of patients. The overall rate of pouch failure was 19.4% (n = 110) at a median follow-up of 15 years; risk factors were female sex, 3-stage approach, and pelvic sepsis. LIMITATIONS: A retrospective database was used. CONCLUSION: Patients with IPAA maintain good pouch function even after 30 years and in patients over the age of 80 years. Pouch function declines with time and failure rates increase over time. See Video Abstract at http://links.lww.com/DCR/B684 . Función De La Bolsa Ileal En El Tiempo Y En Pacientes De Edad Avanzada ANTECEDENTES: No se han efectuado estudios en pacientes con bolsa a largo plazo que incluyan un seguimiento por treinta años o más y en pacientes mayores de 80 años. OBJETIVO: Investigar la funcionalidad o la falla de la bolsa en pacientes bolsa in situ por mas de treinta años y en pacientes mayors de 80 años. DISEÑO: Revisión retrospective. ESCENARIO: Centro de referencia de Enfermedad Inflamatoria Intestinal. PACIENTES: Pacientes adultos con diagnóstico de colitis ulcerative sometidos a anastomosis bolsa ileal anal (IPAA) entre 1983 y 1990. PRINCIPALES PARAMETROS DE RESULTADOS: Indices de efectividad y disfunción de la bolsa ileal. METODOS: Recopilación de la información incluyendo diagnóstico, edad del procedimiento (IPAA), indicaciones para IPAA, medicamentos para IPAA, patología en el transcurso del IPAA, morbilidad postoperatoria, resultados funcionales, calidad de vida, excisión de la bolsa o ileostomía y su indicación y fecha de seguimiento mas reciente. Se contactaron a todos los pacientes vivos en abril de 202 para recuperar la información de los índices de funcionalidad o disfunción de la bolsa. RESULTADOS: Se les construyó una bolsa a un total de 566 pacientes entre 1983 y 1990; de los 145 mas recientemente contactados, 75 permanecían con su bolsa in situ ≥ 30 años y 14 eran mayores de 80 años. La edad media en el momento de diagnóstico fue de 25.8 años (con desviación estándar de 10.6, sd), edad al momento de la cirugía fue de 34.7 años (11.3sd), y la edad en el último seguimiento de 60.5 años (13.2, sd). A una media de 30 años (IQR: 21, 32), 145 pacientes respondieron al cuestionario de funcionalidad. En pacientes mayores de 80 años se observaron tasas aumentadas de urgencia (siempre, la mayor parte de las veces, algunas veces: 71.5% vs 23.5%) y fuga durante el día (71.4% versus 22.4%). En pacientes mayores de 80 años con una bolsa in situ durante 30 años o más, experimentaron urgencia e incontinencia en cerca del 50% y disfunción de la bolsa en un tercio de los pacientes. La tasa global de fallo de la bolsa fue de 19.4% ( n = 110) en un seguimiento a 15 años; los factores de riesgo asociados fueron: sexo femenino, abordaje de tres tiempos y sepsis pélvica. LIMITACIONES: Información retrospective. CONCLUSIONES: Los pacientes con IPAA continúan con una función adecuada de la bolsa aún después de 30 años de efectuada así como en pacientes mayores de 80 años. La funcionalidad de la bolsa disminuye con el tiempo y las tasa de falla aumentan de igual forma con el tiempo. Consulte Video Resumen en http://links.lww.com/DCR/B684 . (Traducción— Dr. Miguel Esquivel-Herrera ) Abstract : Supplemental Digital Content is available in the text.